2017
DOI: 10.1002/jbt.21970
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow and adipose mesenchymal stem cells attenuate cardiac fibrosis induced by methotrexate in rats

Abstract: Mesenchymal stem cells (MSCs) are an ideal adult stem cell with capacity for self-renewal and differentiation with an extensive tissue distribution. The present study evaluates the therapeutic effects of bone marrow mesenchymal stem cells (BM-MSCs) or adipose-derived mesenchymal stem cells (AD-MSCs) against the development of methotrexate (MTX)-induced cardiac fibrosis versus dexamethasone (DEX). Rats were allocated into five groups; group 1, received normal saline orally; group 2, received MTX (14 mg/kg/week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…Mediators of Inflammation [59]. The MTX-induced increase of caspase 3 has been reported in multiorgan toxicity [4,25,53,60,61]. Our results showed a significant increase in caspase 3 expression in response to MTX treatment.…”
supporting
confidence: 64%
“…Mediators of Inflammation [59]. The MTX-induced increase of caspase 3 has been reported in multiorgan toxicity [4,25,53,60,61]. Our results showed a significant increase in caspase 3 expression in response to MTX treatment.…”
supporting
confidence: 64%
“…Methotrexate has a broad spectrum of side effects, including hematological, gastrointestinal, hepatic and renal toxicities as well as lung fibrosis and cardiac damage . Various preclinical studies investigated regenerative effects of MSCs on methotrexate‐induced cardiac and pulmonary fibrosis, kidney and liver injury and have shown beneficial effects regarding organ regeneration and parenchymal functions . However, as most animal work has been done with allogeneic MSCs, further studies are required to investigate if the observed benefits can also be reproduced with pre‐exposed autologous stem cells.…”
Section: Effects Of Chemotherapeutic Anti‐cancer Agents On Mscsmentioning
confidence: 99%
“…This evidenced that coagulation and inflammation here were dual systems playing pivotal roles in host defense against MTX-induced lung injury. The elevation of inflammatory mediators in this study might be due to the increase in the stimulation of Toll-like receptor 2 on resident macrophages by MTX which in turn enhanced the emission of proinflammatory cytokines [9,23]. Thus, it was considered that increased inflammation can intensify coagulation that, in turn, boosted inflammation [24,25].…”
Section: Discussionmentioning
confidence: 74%
“…Bone marrow mesenchymal stem cells (MSCs) arise as an attractive alternative to classic pharmacological treatments. In addition to their ability for differentiation and proliferation, MSCs showed potential anti-inflammatory effects [8,9]. Although several studies evaluated the role of MSCs in MTX-induced lung injury models [10,11], no studies scoped on the modulatory effects of MSCs on coagulation as a risk of thrombosis in such models.…”
Section: Introductionmentioning
confidence: 99%